Reformasi Birokrasi dalam Upaya Pemberantasan Korupsi di Kabupaten Batang (Kepemimpinan Yoyok Riyo Sudibyo, Periode 2012 – 2017) - Mashun Mukromin Ahmad; Teguh Yuwono; Neny Marlina (Journal of Politic and Government Studies, 2017)
Bureaucracy reform is an attempt to reform and change the governance system that concerns the aspects of human resources and work procedures. The spirit of reform is basically contained in the vision of Batang District